Evaluation of knowledge about antibiotics and engagement with a research experience on antimicrobial resistance between pre-university and university students for five school years (2017–2021) - Tarín-Pelló, Antonio; Suay-García, Beatriz; Marco-Crespo, Elisa; Galiana-Roselló, Carolina; Bueso-Bordils, Jose I.; Pérez-Gracia, María-Teresa (Frontiers in Microbiology, 2022)
Antimicrobial resistance remains a serious global health problem. Spain is the fifth country in Europe with the highest consumption of antibiotics, due in part to ignorance of the good use of these drugs and the problem of antimicrobial resistance. In order to avoid a post-antibiotic era, adequate training on this problem is key to create social awareness. The aims of this study were to evaluate the impact that the SWICEU project, an academic program about antibiotic discovery, has had on the knowledge of antimicrobial resistance and rational use of antimicrobials in pre-university students from 7 schools in the province of Valencia during 5 academic years (2017-2021), as well as to evaluate the level of satisfaction of university and pre-university students who have participated in the project. For this study, a survey was carried out with multiple-choice questions with a single correct answer to evaluate the knowledge acquired by pre-university students before and after the project. A satisfaction survey was also designed with Likert scale from lowest to highest level of satisfaction for the two groups of students after the project. Data on knowledge surveys indicated an increase in the mean number of correct answers after the sessions. On satisfaction surveys, we highlighted the issue that referred to the project's recommendation. The data obtained confirms this project as a valuable activity seeing as it allows learning about antimicrobial resistance and the rational use of antibiotics in a pleasing and attractive way for young pre-university and university students.